Managerial discretions and loan loss provisions in Nigerian banks: Empirical IFRS and risk evidence - Abdulai Agbaje Salami; Ahmad Bukola Uthman; Ruth Oluwayemisi Owoade (The Central European Review of Economics and Management (CEREM), 2022)
Aim: The high level of non-performing exposures and the existing crisis in the Nigerian banking sector is a source of concern. To create a basis for solving the troubles caused by the loan loss crisis, this study investigated the managerial discretionary use of loan loss provisions (LLPs) by Nigerian deposit money banks (DMBs). This is considered in the context of solvency risk and reforms embedded in the adoption of International Financial Reporting Standards (IFRSs). Design/research methods: Datasets related to the variables of the study were hand-collected from annual reports of a sample of 16 Nigerian deposit money banks over the period of 2007-2017. The analyses were performed using principal components analysis to derive the managerial discretions index (MDI), Prais-Winsten ordinary least square regression to segregate LLP into reported LLPs (TLLP) and discretionary LLPs (DLLP) and appropriate panel data regression models to test the study's hypotheses subsequent to series of diagnostic tests. Conclusions/findings: The results revealed that managerial discretions negatively influence TLLP and DLLP represented by absolute value of DLLP (ADLLP). This represents an increase in profitability without manipulatingloan loss provisions. However, the reforms embedded in IFRSs revealed the use of LLPs for managerial discretions despite reduction in provisioning level noticeable during IFRS. The situation of Nigerian banks threatened by solvency risk use of LLPs for managerial discretions while attempting to increase profit was exemplified in the increase in ADLLP rather than TLLP. However, improvement was noticeable for risky Nigerian banks during IFRS. The managerial discretionary use of LLPs especially during IFRS was engendered by use of LLPs for capital management and earnings smoothing rather than earnings signalling as further revealed. This shows that adoption of International Financial Reporting Standards reduces reporting quality of Nigerian banks in their loan loss decisions. Originality/value of the article: The derivation of MDI from measures of earnings smoothing, capital management and earnings signalling is the study's contribution to accounting for loan losses literature. The adjustments to LLPs to reduce variability of earnings, meet up with minimum regulatory bank capital adequacy ratio and signal strength to absorb future losses encapsulate earnings smoothing, capital management and earnings signalling respectively. Implications of the research: The discretionary use of LLPs found in this study beckons an increased level of surveillance, oversights and reforms on the part of the regulators for compliance level devoid of managerial opportunistic behaviour to be identifiablewith Nigerian banks.
Keywords: D22; G21; G28; L20; M41; 330; Deposit money banks; IFRSs; loan loss provisions; managerial discretions; solvency risk